Synergistic rust stain removal composition and method for removing rust stain from fabric

The combination of oxalic acid and ascorbic acid and other additives are combined with other additives to form a synergistic rust stain removal composition, solving the problems of hydrofluoric acid hazards and fabric damage, and achieving efficient and safe rust stain removal effect.

CN119234034APending Publication Date: 2024-12-31DIVERSEY INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380039858.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-17
Filing Date
2023-03-15
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Hydrofluoric acid commonly used in existing rust stain removers is dangerous and corrosive, unable to effectively remove rust stains on fabrics and causes damage to the fabrics, and there are safety hazards in its use.

Method used

The combination of oxalic acid and ascorbic acid is used as the rust stain remover. The rust stain is removed by contacting the fabric for a relatively short time (such as 5 minutes), and combined with pH adjusters, organic solvents, surfactants and other additives to form an enhanced effect. Rust stain removal composition.

Benefits of technology

It realizes efficient removal of rust stains in a short period of time, reduces the harm to fabrics and human skin, and provides at least the same rust removal effect as hydrofluoric acid aqueous solution, while reducing fabric damage and significantly reducing the safety risks of users.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119234034A_ABST
    Figure CN119234034A_ABST
Patent Text Reader

Abstract

A synergistic rust removal composition for fabrics comprising: oxalic acid in an amount greater than about 1% by weight but less than about 13% by weight; ascorbic acid in an amount greater than about 0.5% but less than 7% by weight, each based on the total weight of the composition; and water. Also disclosed is a method of removing rust stains from a fabric comprising contacting a fabric with such a synergistic rust stain removal composition. Further disclosed is a method of removing rust stains from a fabric comprising contacting the fabric with a first aqueous solution comprising about 0.5% to about 6% by weight of ascorbic acid based on the total weight of the first aqueous solution; and contacting the fabric with a second aqueous solution comprising about 1% to about 12% by weight of oxalic acid based on the total weight of the second aqueous solution.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Indian Provisional Application No. 202211014841 filed on March 17, 2022. Technical Field

[0003] The present disclosure relates to synergistic rust removing compositions and methods for removing rust stains from fabrics. Background Art

[0004] Rust stains on fabric articles are iron (III) oxide salts. Iron (III) oxide salts are insoluble in water and therefore cannot be removed from fabric articles by conventional laundry / fabric washing operations. Additional steps are required in the laundry operation to effectively remove rust stains from fabric articles. Typically, rust stained fabric articles are pre-treated with a rust stain remover prior to the laundry operation.

[0005] Conventional rust stain removers typically include hydrofluoric acid as an active ingredient, such as those manufactured by Rust-Oleum Corporation. A rust stain remover which is an aqueous solution containing from about 1 weight percent to about 3 weight percent hydrofluoric acid based on the total weight of the solution, or manufactured by AL Wilson Chemical Company Rust remover, which is an aqueous solution of hydrofluoric acid containing about 5% by weight to about 10% by weight based on the total weight of the solution. It is well known that hydrofluoric acid can effectively remove rust stains from fabrics within a short contact time (such as five minutes). However, hydrofluoric acid is extremely dangerous and corrosive, and even in very small amounts, it can still cause severe burns when in contact with human skin. It is recorded that hydrofluoric acid can penetrate human skin and degrade the underlying bones. In addition, hydrofluoric acid can also have a negative impact on fabric fibers, causing fabric damage, thereby shortening the service life of fabric products.

[0006] There is a need for a rust stain removal composition that neither damages fabric articles nor causes severe burns when in contact with human skin, and yet provides at least the same rust removal effectiveness as conventional rust stain removers (eg, aqueous hydrofluoric acid). Summary of the invention

[0007] In a first aspect, a synergistic rust stain removal composition is disclosed, comprising oxalic acid in an amount greater than about 1% by weight but less than about 13% by weight based on the total weight of the composition; ascorbic acid in an amount greater than about 0.5% by weight but less than about 7% by weight based on the total weight of the composition; and water. In some embodiments, oxalic acid is present in an amount greater than about 6% by weight but less than about 13% by weight based on the total weight of the composition. In some embodiments, oxalic acid is present in an amount of about 2% by weight to about 12% by weight, preferably about 3% by weight to about 12% by weight, and most preferably about 7% by weight to about 12% by weight, based on the total weight of the composition. In some embodiments, ascorbic acid is present in an amount of about 1% by weight to about 6% by weight, based on the total weight of the composition. In some embodiments, the synergistic rust stain removal composition comprises about 7% by weight to about 12% by weight of oxalic acid; about 1% by weight to about 6% by weight of ascorbic acid; and water, based on the total weight of the composition. In some embodiments, the synergistic rust stain removal composition further comprises a pH adjuster, an organic solvent, a surfactant, a chelating agent, an acrylic polymer, an oxidizing agent, a fragrance, a dye, or any combination thereof.

[0008] In some embodiments, the synergistic rust stain removal composition consists of oxalic acid in an amount greater than about 1% by weight but less than about 13% by weight based on the total weight of the composition; ascorbic acid in an amount greater than about 0.5% by weight but less than about 7% by weight based on the total weight of the composition; water; and optionally at least one additive selected from a pH adjuster, an organic solvent, a surfactant, a chelating agent, an acrylic polymer, an oxidizing agent, a fragrance, a dye, or any combination thereof. In certain embodiments, oxalic acid is present in an amount of about 2% by weight to about 12% by weight, preferably about 7% by weight to about 12% by weight, based on the total weight of the composition. In certain embodiments, ascorbic acid is present in an amount of about 2% by weight to about 6% by weight, based on the total weight of the composition.

[0009] In some embodiments, the synergistic rust stain removal composition does not contain hydrogen peroxide, inorganic acids (such as hydrofluoric acid, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, boric acid, etc.), other organic acids other than oxalic acid and ascorbic acid (such as formic acid, acetic acid, fumaric acid, citric acid, malic acid, tartaric acid, ethane-1-hydroxy-1,1'-diphosphonic acid, fatty acids, etc.), fluorine-based salts (such as calcium fluoride, sodium fluoride, ammonium bifluoride, etc.) or any combination thereof.

[0010] In a second aspect, a method for removing rust stains from a fabric is provided, the method comprising contacting the fabric with the above-mentioned synergistic rust stain removal composition. In some embodiments, the fabric is contacted with the rust stain removal composition for about 1 minute to about 20 minutes, preferably about 5 minutes. In some embodiments, the contact time is 5 minutes and the method provides a rust removal rate percentage of at least 50%, the rust removal rate percentage being calculated based on the reflectivity of the fabric at a wavelength of 460 nanometers. In some embodiments, the contact time is 5 minutes and the fluidity value of the fabric before and after contact with the rust stain removal composition changes by no more than 25%, the fluidity value change being determined according to Indian Standard IS244 (1984) (Second Revision, Re-determined in 2006).

[0011] In a third aspect, a method for removing rust stains from a fabric is provided, the method comprising contacting the fabric with a first aqueous solution, the first aqueous solution comprising about 0.5% by weight to about 6% by weight of ascorbic acid based on the total weight of the first aqueous solution; and contacting the fabric with a second aqueous solution, the second aqueous solution comprising about 1% by weight to about 12% by weight of oxalic acid based on the total weight of the second aqueous solution. In some embodiments, the method comprises contacting the fabric with the first aqueous solution, followed by contacting the fabric with the second aqueous solution. In some embodiments, the method comprises contacting the fabric with the second aqueous solution, followed by contacting the fabric with the first aqueous solution. In some embodiments, the method comprises contacting the fabric with the first aqueous solution and the second aqueous solution simultaneously. The fabric may be contacted with the first aqueous solution and the second aqueous solution for about 1 minute to about 20 minutes, preferably about 5 minutes. In addition, the fabric may be contacted with the first aqueous solution and the second aqueous solution at room temperature. In some embodiments, the method provides a rust removal percentage of at least 50%, the rust removal percentage being calculated based on the reflectivity of the fabric at a wavelength of 460 nanometers. In some embodiments, the fluidity value of the fabric before and after contacting with the rust stain removal composition changes by no more than 25%, as determined in accordance with Indian Standard IS244 (1984) (Second Revision, Redetermined in 2006).

[0012] Other aspects of the disclosure will become apparent through consideration of the detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 A graph is plotted for the relationship between the amount of ascorbic acid in the rust stain removal composition (reported as weight percent based on the total weight of the rust stain removal composition) and the rust removal efficacy on fabric (reported as reflectance R460 value). DETAILED DESCRIPTION

[0014] In general, the present disclosure relates to a synergistic rust stain removal composition that can effectively remove rust stains from surfaces, especially from fabrics, within a relatively short contact time (e.g., 5 minutes of contact time). The disclosed synergistic rust stain removal composition causes less damage to fabrics and reduces safety concerns for users, but provides at least the same level of rust stain removal as conventional rust stain removers using hydrofluoric acid as an active ingredient. The present disclosure also relates to a method for removing rust stains from fabrics, which exhibits unexpected synergistic enhancement of rust removal.

[0015] As used herein, the terms "comprise," "comprising," "include," "including," "having," "has," "contain," and "containing," and variations thereof, are open transitional phrases, terms, or words that are intended to encompass the items listed thereafter and equivalents thereof, as well as additional items. The singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. When the term "comprising" is used, whether or not explicitly stated, the disclosure also contemplates other embodiments that "comprise," "consist of," or "consist essentially of," the elements presented herein.

[0016] Any numerical range stated herein includes all values ​​from the lower limit to the upper limit. For example, if the stated concentration range is 1% to 50%, it is intended that values ​​such as 2% to 40%, 10% to 30%, or 1% to 3% are explicitly listed in this specification. These are just examples of specific intent, and all possible numerical combinations between (including the lowest and highest values) listed should be considered to have been explicitly stated in this application.

[0017] The modifier "about" used in conjunction with a quantity is inclusive of the stated value and has a meaning determined by the context (e.g., it includes at least the degree of error associated with the measurement of that particular quantity). The term "about" means plus or minus 10% of the number indicated. For example, "about 10%" means a range of 9% to 11%, and "about 1" means 0.9 to 1.1. Other meanings of "about" may be apparent from the context, such as rounding, so that, for example, "about 1" also means 0.5 to 1.4.

[0018] As used herein, the terms "weight percent," "wt %," "percent by weight," "% weight," and variations thereof refer to the concentration of a component expressed as the weight of the component divided by the total weight of the composition multiplied by 100. Unless otherwise indicated, all concentrations are expressed as weight percent concentrations.

[0019] The term "substantially free" means that the composition does not contain a specific compound, or the specific compound is not intentionally added to the composition. If the specific compound is present through contamination, the amount of the specific compound should be less than 0.5% by weight, preferably less than 0.1% by weight based on the total weight of the composition.

[0020] The term "fabric" as used herein refers to any woven, nonwoven, knitted, felted material or any combination thereof produced from or combined with any natural fiber, regenerated fiber, synthetic fiber or substitute thereof. Non-limiting examples of natural fibers are cotton and wool fibers. Non-limiting examples of regenerated fibers are viscose fibers and rayon. Non-limiting examples of synthetic fibers are polyester, polyamide (also known as nylon) and polyacrylic fibers.

[0021] The term "fiber" as used herein refers to materials that can be spun into yarn or made into fabric by bonding or by interlacing in various ways including, but not limited to, weaving, knitting, braiding, felting, twisting, webbing, or any combination thereof.

[0022] As used herein, the term "yarn" refers to bundles of textile fibers in a form suitable for weaving, knitting, braiding, felting, twisting, webbing, or otherwise forming into a fabric.

[0023] As used herein, the term "reflectance R460 value" refers to the reflectance of a fabric at a wavelength of 460 nanometers.

[0024] In a first aspect of the present disclosure, a rust stain removal composition comprises:

[0025] oxalic acid in an amount greater than about 1 weight percent but less than about 13 weight percent based on the total weight of the composition;

[0026] Ascorbic acid in an amount greater than about 0.5 weight percent but less than 7 weight percent based on the total weight of the composition; and

[0027] water.

[0028] For oxalic acid, in some embodiments, oxalic acid is present in an amount greater than about 1%, about 1.5%, about 2%, about 2.5%, about 3%, about 3.5%, about 4%, about 4.5%, about 5%, about 5.5%, about 6%, about 6.25%, about 6.5%, about 6.75%, about 7%, or about 7.25% by weight based on the total weight of the rust stain removal composition; and / or less than about 7.5%, about 8%, about 8.5%, about 9%, about 9.5%, about 10%, about 10.5%, about 11%, about 11.5%, about 12%, about 12.25%, about 12.5%, about 12.75%, or about 13% by weight based on the total weight of the rust stain removal composition. In some embodiments, oxalic acid is present in an amount greater than about 6% by weight but less than about 13% by weight based on the total weight of the composition.

[0029] In some embodiments, oxalic acid is present in an amount of about 2%, about 2.5%, about 3%, about 3.5%, about 4%, about 4.5%, about 5%, about 5.5%, about 6%, about 6.25%, about 6.5%, about 6.75%, about 7%, or about 7.25% by weight to about 7.5%, about 8%, about 8.5%, about 9%, about 9.5%, about 10%, about 10.5%, about 11%, about 11.5%, about 12%, about 12.25%, about 12.5%, or about 12.75% by weight based on the total weight of the rust stain removal composition.

[0030] In some embodiments, oxalic acid is present in an amount of about 2 weight % to about 12 weight % based on the total weight of the rust stain removal composition. In some embodiments, oxalic acid is present in an amount of about 3 weight % to about 12 weight % based on the total weight of the rust stain removal composition. In some embodiments, oxalic acid is present in an amount of about 7 weight % to about 12 % based on the total weight of the rust stain removal composition.

[0031] For ascorbic acid, in some embodiments, the ascorbic acid is present in an amount greater than about 0.5%, about 0.75%, about 1%, about 1.25%, about 1.5%, about 1.75%, about 2%, about 2.25%, about 2.5%, about 2.75%, or about 3% by weight based on the total weight of the rust stain removal composition; and / or less than about 3.25%, about 3.5%, about 3.75%, about 4%, about 4.25%, about 4.5%, about 4.75%, about 5%, about 5.25%, about 5.75%, about 6%, about 6.25%, about 6.5%, about 6.75%, or about 7% by weight based on the total weight of the rust stain removal composition.

[0032] In some embodiments, ascorbic acid is present in an amount of about 0.75%, about 1%, about 1.25%, about 1.5%, about 1.75%, about 2%, about 2.25%, about 2.5%, about 2.75%, or about 3% by weight based on the total weight of the rust stain removal composition to about 5%, about 5.25%, about 5.75%, about 6%, about 6.25%, about 6.5%, or about 6.75% by weight based on the total weight of the rust stain removal composition. In some embodiments, ascorbic acid is present in an amount of about 1% by weight to about 6% by weight based on the total weight of the rust stain removal composition.

[0033] In some embodiments, the disclosed rust stain removal composition comprises about 7 wt % to about 12 wt % oxalic acid; about 1 wt % to about 6 wt % ascorbic acid; and water, all based on the total weight of the rust stain removal composition.

[0034] In some embodiments, the disclosed rust stain removal composition further comprises a pH adjuster, an organic solvent, a surfactant, a chelating agent, an acrylic polymer, an oxidizing agent, a fragrance, a dye, or any combination thereof. Non-limiting examples of suitable pH adjusters are aminosulfonic acid, ethanolamine, sodium bisulfite, etc. Non-limiting examples of organic solvents are glycol ethers, alcohols, ethylene glycol, etc.

[0035] When desired, the surfactant may include anionic surfactants, nonionic surfactants, or any combination thereof. Non-limiting examples of anionic surfactants are sodium dodecyl sulfate, sodium alkylbenzene sulfonate, and the like.

[0036] In certain embodiments, the disclosed rust stain removal composition consists of:

[0037] oxalic acid in an amount greater than about 1 weight percent but less than about 13 weight percent based on the total weight of the composition;

[0038] ascorbic acid in an amount greater than about 0.5 weight percent but less than 7 weight percent based on the total weight of the composition;

[0039] water; and

[0040] The optional at least one additive is selected from a pH adjuster, an organic solvent, a surfactant, a chelating agent, an acrylic polymer, an oxidizing agent, a fragrance, a dye or any combination thereof.

[0041] In some embodiments, the disclosed rust stain removal composition does not contain hydrogen peroxide, inorganic acids, other organic acids other than oxalic acid and ascorbic acid, fluorine-based salts, or any combination thereof. Non-limiting examples of such inorganic acids are hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, boric acid, and the like. Non-limiting examples of such other organic acids are formic acid, acetic acid, fumaric acid, citric acid, malic acid, tartaric acid, ethane-1-hydroxy-1,1'-diphosphonic acid (HEDP), fatty acids, and the like. Non-limiting examples of such fluorine-based salts are calcium fluoride, sodium fluoride, ammonium bifluoride, and the like.

[0042] In a second aspect of the present disclosure, a method for removing rust stains from a fabric comprises contacting the fabric with the above-mentioned rust stain removal composition. The contact time between the fabric and the disclosed rust stain removal composition can be from about 1 minute to about 20 minutes. In some embodiments, the contact time is about 5 minutes. In addition, the fabric can be contacted with the first aqueous solution and the second aqueous solution at room temperature.

[0043] The efficacy of the rust stain removal composition in removing rust stains from fabrics can be determined based on the reflectance of the fabric at a wavelength of 460 nanometers (hereinafter referred to as the "reflectance R460 value"). The higher the reflectance R460 value, the higher the whiteness of the fabric, and therefore the greater the efficacy of the rust stain removal composition in removing rust stains from fabrics. In addition, the following equation can be used to quantify based on the reflectance R460 value of the fabric:

[0044]

[0045] in

[0046] RV T is the reflectance R460 value of the rust-stained fabric sample after treatment with the rust stain removal composition, and

[0047] RV R It is the reflectance R460 value of a clean fabric swatch without any treatment with the rust stain removing composition.

[0048] In some embodiments, the contact time between the fabric and the rust stain removal composition is 5 minutes, and the disclosed method provides a rust removal percentage of at least about 50%, the rust removal percentage being calculated based on the reflectance of the fabric at a wavelength of 460 nanometers.

[0049] The level of fabric damage caused by the treatment of the fabric can be determined based on the change in the fluidity value of the fabric before and after treatment with the rust stain removal composition. The fluidity value of the fabric is measured according to Indian Standard IS244 (1984): Method for Determination of Viscosity (or Fluidity) of Solutions of Cotton and Regenerated Cellulosic Man-Made Fibers in Cuprammonium Hydroxide (Second Revision, Re-determined in 2006), which is incorporated herein by reference (hereinafter referred to as "Indian Standard IS244 Method"). According to the Indian Standard IS244 method, the fluidity value of the fabric is linearly related to the percentage loss of tensile strength of the fabric caused by chemical action (e.g., treatment with a rust stain removal composition). Therefore, the level of fabric damage caused by the rust removal treatment can be quantified based on the percentage change in the fluidity value of the fabric before and after treatment as shown in the following formula:

[0050]

[0051] in

[0052] FV Tis the flowability value of the rust-stained fabric sample after being treated with the rust stain removal composition,

[0053] FV R is the flowability value of the rust-stained fabric sample before treatment with the rust stain removing composition.

[0054] Higher variation in the % flowability value of the fabric as measured according to Indian Standard IS244 method indicates higher level of fabric damage caused by the descaling treatment.

[0055] In some embodiments, the contact time between the fabric and the rust stain removal composition in the disclosed methods is 5 minutes, and the flowability value of the fabric before and after the contacting does not change by more than about 25%.

[0056] In some embodiments, the contact time between the fabric and the rust stain removal composition is 5 minutes, the disclosed method provides a rust removal rate percentage of at least 50%, the rust removal rate percentage is calculated based on the reflectance of the fabric at a wavelength of 460 nanometers, and the fluidity value of the fabric before and after the contacting does not change by more than 25%, and the fluidity value change is determined according to the Indian Standard IS244 method.

[0057] The disclosed rust stain removal composition provides an unexpected synergistic effect (synergistic effect) between oxalic acid and ascorbic acid in removing rust stains from fabrics even at relatively short contact times (e.g., about 5 minutes of contact time between the fabric and the rust stain removal composition). The synergistic effect can be achieved when the amount of oxalic acid in the rust stain removal composition is greater than 1 wt % but less than 13 wt % based on the total weight of the composition. As a non-limiting example shown in Example 1 and Table 1A of the Examples section, an unexpected synergistic effect can be achieved when the amount of oxalic acid in the rust stain removal composition is from about 2 wt % to about 12 wt % based on the total weight of the composition.

[0058] Furthermore, surprisingly and unexpectedly, a significant enhancement in rust removal was achieved when the amount of ascorbic acid (when used in combination with oxalic acid) in the rust stain removal composition was greater than 0.5 wt % but less than 7 wt % based on the total weight of the composition. Figure 1 As a non-limiting example shown in , an unexpected and significant increase in % rust removal is achieved when the amount of ascorbic acid (when used in combination with oxalic acid) in the rust stain removal composition is from about 1 wt% to about 6 wt% based on the total weight of the composition. See also Example 3 and Table 3A. This finding is even more unexpected because ascorbic acid (i.e., when used as the sole rust removing active ingredient) by itself exhibits extremely poor rust removal effectiveness, even when the amount of ascorbic acid is increased from 0.5 wt% to 7 wt% (based on the total weight of the composition), its rust removal effectiveness is still only about 8% to 9%. See Example 2 and Table 2.

[0059] The disclosed rust stain removal compositions can provide at least the same level of rust removal efficacy as known rust stain removers, such as ALWilson Chemical Company, NJ (USA). A rust remover containing 10% by weight (based on the total weight of the rust remover) of hydrofluoric acid as an active ingredient ("10% hydrofluoric acid solution"); and an alternative commercially available rust remover for fabrics containing 10% by weight (based on the total weight of the rust remover) of oxalic acid as an active ingredient ("10% oxalic acid solution"). As a non-limiting example shown in Table 5, the 10% hydrofluoric acid solution provides a % rust removal rate of 98%, while the 10% oxalic acid solution only provides a % rust removal rate of 47%. The disclosed rust stain removal composition can provide a % rust removal rate of up to 95%, which is approximately the same level of rust removal effectiveness achieved by the conventional and widely used 10% hydrofluoric acid solution.

[0060] Although conventional rust stain removal compositions (e.g., 10% hydrofluoric acid solutions) are safe when used in accordance with their directions, hydrofluoric acid can still cause severe penetrating burns when it comes in contact with human skin. Hydrofluoric acid-induced burns are often not noticed until the day after contact, when painful ulcers appear on the skin.

[0061] The disclosed rust stain removal composition reduces the potential harmful effects associated with conventional rust stain removal compositions that use hydrofluoric acid as an active ingredient. The disclosed rust stain removal composition utilizes a mixture of oxalic acid and ascorbic acid instead of hydrofluoric acid; thus, the potential harmful effects caused by hydrofluoric acid are reduced.

[0062] In addition, conventional rust stain removal compositions (e.g., 10% hydrofluoric acid solution) can cause damage to fabrics, thereby shortening the useful life of the fabrics. As a non-limiting example shown in Table 1C and Table 3B of the Examples section, the % fluidity value of the stained fabric after treatment with a conventional rust stain removal composition (10% hydrofluoric acid solution) changed by 44%; while the % fluidity value of the stained fabric after treatment with a 10% oxalic acid solution changed by 28%. Therefore, compared with the 10% hydrofluoric acid solution, the 10% oxalic acid solution causes less damage to the fabric. However, as mentioned above, the rust removal effect of the 10% oxalic acid solution is far inferior to that of the 10% hydrofluoric acid solution.

[0063] Compared to 10% hydrofluoric acid solution, the disclosed rust stain removal composition causes significantly less damage to fabrics, and even less damage to fabrics than 10% oxalic acid solution. As non-limiting examples shown in Table 1C and Table 3B, the change in % fluidity value of stained fabrics after treatment with the disclosed rust stain removal composition is less than 25%, and can even be less than 10%. Nevertheless, the rust removal effect of the disclosed rust stain removal composition is substantially the same as that of the 10% hydrofluoric acid solution, and is much better than that of the 10% oxalic acid solution. See Table 5.

[0064] Thus, the disclosed rust stain removal composition provides rust removal at least as effective as conventional rust removers (e.g., 10 wt. % hydrofluoric acid in water), but with significantly less damage to fabrics than conventional rust removers. In addition, the disclosed rust stain removal composition reduces the potential harmful effects associated with conventional rust stain removal compositions that use hydrofluoric acid as an active ingredient.

[0065] In a third aspect of the present disclosure, a method for removing rust stains from a fabric comprises:

[0066] contacting the fabric with a first aqueous solution comprising from about 0.5 weight percent to about 6 weight percent ascorbic acid based on the total weight of the first aqueous solution; and

[0067] The fabric is contacted with a second aqueous solution comprising from about 1 weight percent to about 12 weight percent oxalic acid based on the total weight of the second aqueous solution.

[0068] In some embodiments, the method comprises contacting the fabric with a first aqueous solution and subsequently contacting the fabric with a second aqueous solution.

[0069] In some embodiments, the method comprises contacting the fabric with the second aqueous solution, and subsequently contacting the fabric with the first aqueous solution.

[0070] In some embodiments, the method includes contacting the fabric with a first aqueous solution and a second aqueous solution simultaneously.

[0071] In some embodiments, the first aqueous solution comprises at least about 0.5%, about 1.0%, about 1.5%, about 2%, about 2.5%, about 3%, or about 3.5% by weight based on the total weight of the first aqueous solution; and / or no more than about 4%, about 4.5%, about 5.0%, about 5.5%, or about 6.0% by weight based on the total weight of the first aqueous solution. In some embodiments, the first aqueous solution comprises ascorbic acid in an amount of about 0.5%, about 1.0%, about 1.5%, about 2%, about 2.5%, about 3%, or about 3.5% by weight based on the total weight of the first aqueous solution to about 4%, about 4.5%, about 5.0%, about 5.5%, or about 6.0% by weight based on the total weight of the first aqueous solution.

[0072] In some embodiments, the second aqueous solution comprises at least about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, or about 7% by weight based on the total weight of the second aqueous solution; and / or no more than about 8%, about 9%, about 10%, about 11%, or about 12% by weight of oxalic acid based on the total weight of the second aqueous solution. In some embodiments, the second aqueous solution comprises oxalic acid in an amount of about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, or about 7% by weight based on the total weight of the second aqueous solution to about 8%, about 9%, about 10%, about 11%, or about 12% by weight based on the total weight of the second aqueous solution.

[0073] In some embodiments, the first aqueous solution comprises about 1 wt% to 6 wt% ascorbic acid based on the total weight of the first aqueous solution; and / or about 6 wt% to 12 wt% oxalic acid based on the total weight of the second aqueous solution.

[0074] In the disclosed method of the third aspect, the fabric can be contacted with the first aqueous solution and the second aqueous solution for a time of about 1 minute to about 20 minutes. In some embodiments, the fabric is contacted with the first aqueous solution and the second aqueous solution for about 5 minutes. In addition, the fabric can be contacted with the first aqueous solution and the second aqueous solution at room temperature.

[0075] In some embodiments, the contact time between the fabric and the rust stain removal composition is 5 minutes, and the disclosed method provides a rust removal percentage of at least 50%, the rust removal percentage being calculated based on the reflectance of the fabric at a wavelength of 460 nanometers.

[0076] In some embodiments, the contact time between the fabric and the rust stain removal composition in the disclosed method is 5 minutes, and the flowability value of the fabric before and after contacting does not change by more than about 25%, as determined according to Indian Standard IS244 method.

[0077] In some embodiments, the contact time between the fabric and the rust stain removal composition is 5 minutes, the disclosed method provides a rust removal percentage of at least 50%, the rust removal percentage being calculated based on the reflectance of the fabric at a wavelength of 460 nanometers, and the fluidity value of the fabric before and after contacting does not change by more than about 25%, the fluidity value change being determined according to the Indian Standard IS244 method.

[0078] The disclosed method of removing rust stains from fabrics provides at least the same rust removal effect as a conventional rust stain removal composition (10% hydrofluoric acid solution). As a non-limiting example shown in Example 7 and Table 7A, the 10% hydrofluoric acid solution provides a rust removal percentage of about 98%, while the disclosed rust stain removal composition provides a rust removal percentage of about 100%.

[0079] In addition, the disclosed rust stain removal compositions caused significantly less damage to fabrics than the 10% hydrofluoric acid solution. See Table 7B.

[0080] Thus, the disclosed method of removing rust stains from fabrics provides at least the same level of rust removal as conventional rust stain removers (e.g., 10 wt. % hydrofluoric acid in water), but with significantly less damage to fabrics than conventional rust stain removers. In addition, the disclosed rust stain removal composition reduces the potential harmful effects associated with conventional rust stain removal compositions that use hydrofluoric acid as an active ingredient.

[0081] The following non-limiting examples illustrate the compositions of the present disclosure and methods of using the same.

[0082] Example

[0083] Materials and Procedure

[0084] The fabric used is WFK 11A fabric, which is made of 100% cotton, is a plain weave fabric and does not contain any fluorescent brightener. The weight of the fabric is 170g / m 2 , the warp and weft are 25 threads per centimeter, and the fluidity value is less than 50 Pa.s. The reflectivity ("reflectivity R460 value") and fluidity value of the WKF fabric are measured at a wavelength of 460 nm.

[0085] A WKF fabric of 20 cm x 20 cm in size was placed on a plastic tray. Subsequently, about 100 ml of a 10% FeSO4.7H2O solution was poured into the plastic tray. After 5 minutes of contact, the fabric was removed from the tray and air-dried for 3 hours. The dried fabric was then immersed again in 100 ml of a 10% FeSO4.7H2O solution for five minutes, removed, and then air-dried for about 3 to 4 hours. The resulting fabric was cut into small pieces ("fabric swatches") of 5 cm x 5 cm in size.

[0086] Prepare about 500 ml of 10% (v / v) ammonium hydroxide solution in a beaker. Immerse each fabric swatch in the ammonium hydroxide solution for 20 seconds without touching the beaker wall. The color of the fabric swatch is green because of the formation of Fe 2+ After 20 seconds of contact, the fabric sample was removed from the ammonium hydroxide solution and air-dried. 2+ The ion is slowly oxidized to Fe 3+ ions, the color of the fabric sample slowly changes to the muddy brown of rust stains (Fe 3+After air drying for 24 hours, the fabric swatches were washed in clean tap water to remove any traces of alkali. After the fabric swatches were dried, the reflectance R460 value and fluidity value of the fabric swatches with rust stains were measured and recorded as the reflectance R460 value and the fluidity value before treatment with the tested rust stain removal composition.

[0087] One-step rust removal

[0088] The stained fabric sample was treated with the tested rust stain removal composition by applying the tested rust stain removal composition to the stained fabric sample by spraying, and the amount of the tested rust stain removal composition was sufficient to wet the stained fabric sample. The stained fabric sample was contacted with the tested rust stain removal composition for 5 minutes, and then rinsed with water or subjected to a conventional washing process. The reflectance R460 value and flowability value of the resulting treated fabric sample were measured.

[0089] Two-step rust removal

[0090] In the first step, the stained fabric sample is treated with the first composition by spray application. The first composition is contacted for about 5 seconds or immediately proceeds to the second step. Subsequently, in the second step, the fabric sample is contacted with the second composition for 5 minutes. Thereafter, the treated fabric sample is rinsed with water or subjected to a conventional washing process. The reflectance R460 value and the flowability value of the resulting treated fabric sample are measured.

[0091] Determine the rust removal effectiveness based on reflectivity R460

[0092] The efficacy of the tested rust stain removal compositions in removing rust stains from fabric swatches was determined based on the reflectance of the treated fabric swatches at a wavelength of 460 nm ("Reflectance R460 Value") using a CM-3600d benchtop spectrophotometer available from Konica Minolta Sensing Americas, Inc. A higher Reflectance R460 value indicates a higher level of fabric whiteness and, therefore, a greater efficacy of the tested composition in removing rust stains from fabric. The cleaned fabric swatches exhibited a Reflectance R460 value of about 80±3.

[0093] The rust removal percentage is calculated based on the fabric's reflectance R460 value as shown below:

[0094]

[0095] in

[0096] RV T is the reflectance R460 value of the rust-stained fabric sample after treatment with the rust stain removal composition, and

[0097] RV Ris the reflectance R460 value of a clean fabric sample that does not require treatment with a rust stain removal composition. R The value is 81, which is the average reflectance R460 value of the clean fabric sample that does not require rust removal treatment.

[0098] Determining fabric damage level based on flowability values

[0099] The level of damage to the fabric caused by treatment with the tested rust stain removal composition is determined based on the fluidity value of the treated fabric. The fluidity value of the fabric is determined according to Indian Standard IS244 (1984): Method for Determination of Viscosity (or Fluidity) of Solutions of Cotton and Regenerated Cellulosic Manmade Fibers in Cuprammonium Hydroxide (Second Revision, Re-determined in 2006), which is incorporated herein by reference. The higher the fabric fluidity value measured according to the Indian Standard IS244 method, the higher the percentage loss of tensile strength of the fabric caused by treatment with the tested rust stain removal composition.

[0100] According to Indian Standard IS244 method, the fluidity value is the reciprocal of the viscosity of the cuprammonium hydroxide solution of the treated fabric, expressed in poise. -1 The unit is recorded. A weighed sample of the treated fabric swatch is dissolved in the cuprammonium hydroxide solution in the viscometer to provide a fabric solution. The temperature of the viscometer and its contents is adjusted to 20±1° C. in a thermostat. The fabric solution is allowed to flow from the viscometer through the capillary. The time required for the meniscus of the fabric solution to fall from one fixed mark to another fixed mark is recorded and the fluidity is subsequently determined according to the Indian Standard IS244 method.

[0101] The level of fabric damage caused by the rust removal treatment can be quantified based on the percent change in the flowability value of the fabric before and after treatment as shown in the following formula:

[0102]

[0103] in

[0104] FV T is the flowability value of the rust-stained fabric sample after being treated with the rust stain removal composition,

[0105] FV R is the flowability value of the rust-stained fabric sample before treatment with the rust stain removing composition.

[0106] Example 1

[0107] The rust stain removal composition was used to remove rust from the rust stained fabric sample using a one-step method. The treatment lasted for 5 minutes. The efficacy of the rust stain removal composition in removing rust stains from the stained fabric sample was determined based on the reflectance R460 value.

[0108]

[0109] Table 1A shows the reflectance R460 values ​​of the fabric swatches after treatment with the tested rust stain removal compositions.

[0110] Test composition #1A contains ascorbic acid as the only rust-removing active ingredient, as well as aminosulfonic acid, ethanolamine, sodium lauryl sulfate as a surfactant, ethylene glycol ether as an organic solvent, and the balance of water. The average reflectance R460 value of the stained fabric sample treated with test composition #1A is 8.23, which corresponds to a rust removal rate of about 10%.

[0111] Test composition #1B is a 1% by weight aqueous solution of oxalic acid based on the total weight of the solution and contains oxalic acid as the only rust removing active ingredient. The average reflectance R460 value of the stained fabric swatches treated with test composition #1B was 9.43, which corresponds to a rust removal rate of about 12%.

[0112] Test composition #1C is essentially a combination of test compositions #1A and #1B and contains both ascorbic acid and oxalic acid as rust removing active ingredients. The average reflectance R460 value of the stained fabric swatches treated with test composition #1B was 18.47, which corresponds to a rust removal rate of about 23%.

[0113] The rust removal efficiency of Test Composition #1C was about 23%, which was approximately the sum of the rust removal efficiency of 10% from Test Composition #1A (ascorbic acid as the only rust removal active ingredient) and the rust removal efficiency of 12% from Test Composition #1B (oxalic acid as the only rust removal active ingredient). Therefore, when the oxalic acid concentration was 1% by weight (based on the total weight of the tested rust stain removal composition), no synergistic effect between ascorbic acid and oxalic acid on rust removal efficacy was observed.

[0114] Test composition #1D is an aqueous solution containing 2% by weight (based on the total weight of the solution) of oxalic acid as a rust-removing active ingredient. The average reflectance R460 value of the stained fabric swatches treated with test composition #1D was 14.19, which corresponds to a rust removal rate of about 18%.

[0115] Test composition #1E is essentially a combination of test compositions #1A and #1D and contains both ascorbic acid and oxalic acid as rust removing active ingredients. The average reflectance R460 value of the stained fabric swatches treated with test composition #1E was 28.76, which corresponds to a rust removal rate of about 36%.

[0116] If the rust removal effect between oxalic acid and ascorbic acid was merely additive, it would be expected that the % rust removal for Test Composition #1E would be about 28%, which is the cumulative value of the rust removal from Test Composition #1A of about 10% and the rust removal from Test Composition #1D of about 18%. However, the rust removal for Test Composition #1E was about 36%, which is higher than the cumulative rust removal of 28%. Therefore, there is a synergistic effect between ascorbic acid and oxalic acid in rust removal effectiveness when the oxalic acid concentration is 2% by weight (based on the total weight of the tested rust stain removal composition).

[0117] Test composition #1F is an aqueous solution containing 7% by weight (based on the total weight of the solution) of oxalic acid as a rust-removing active ingredient. The average reflectance R460 value of the stained fabric swatches treated with test composition #1D was 26.91, which corresponds to a rust removal rate of about 33%.

[0118] Test composition #1G is essentially a combination of test compositions #1A and #1F and contains both ascorbic acid and oxalic acid as rust removing active ingredients. The average reflectance R460 value of the stained fabric swatches treated with test composition #1G was 77.17, which corresponds to a rust removal rate of about 95%.

[0119] The approximately 95% rust removal achieved by Test Composition #1G is more than twice the cumulative rust removal of approximately 43% (the cumulative value of the rust removal of approximately 10% from Test Composition #1A and the rust removal of approximately 33% from Test Composition #1F). Therefore, when the oxalic acid concentration is 7% by weight (based on the total weight of the tested rust stain removal composition), there is a synergistic effect between ascorbic acid and oxalic acid in rust removal effectiveness.

[0120] Test composition #1H is an aqueous solution containing 12% by weight (based on the total weight of the solution) of oxalic acid as a rust-removing active ingredient. The average reflectance R460 value of the stained fabric swatches treated with test composition #1H was 36.80, which corresponds to a rust removal rate of about 45%.

[0121] Test composition #1J is essentially a combination of test compositions #1A and #1H and contains both ascorbic acid and oxalic acid as rust removing active ingredients. The average reflectance R460 value of the stained fabric swatches treated with test composition #1J was 74.96, which corresponds to a rust removal rate of about 93%.

[0122] The rust removal rate of about 93% obtained by Test Composition #1J was higher than the cumulative rust removal rate of about 55% (the cumulative value of the rust removal rate of about 10% from Test Composition #1A and about 45% from Test Composition #1H). Therefore, when the oxalic acid concentration is 12% by weight (based on the total weight of the tested rust stain removal composition), there is a synergistic effect between ascorbic acid and oxalic acid in rust removal effectiveness.

[0123] As shown in Test Composition #1K of Table 1A, when the oxalic acid concentration was about 13% by weight, the test composition was unstable and precipitated.

[0124] Table 1B shows the comparative rust removal efficacy of the tested rust stain removal compositions. The reference is a clean fabric sample that did not require rust removal treatment. Two known rust stain removal compositions were used for the comparative study: A rust remover, which is widely used and is considered to be a conventional fabric rust remover, which contains 10% by weight (based on the total weight of the rust remover) of hydrofluoric acid as an active ingredient (hereinafter referred to as "10% hydrofluoric acid solution"); and another commercially available fabric rust remover, which contains 10% by weight (based on the total weight of the rust remover) of oxalic acid as an active ingredient (hereinafter referred to as "10% oxalic acid solution").

[0125] Table 1B

[0126]

[0127]

[0128] The reference is a clean fabric sample without rust removal treatment, and its average reflectance R460 value is 81. It is expected that the reflectance R460 value of the fabric sample after rust removal treatment is as close to 81 as possible. The reflectance R460 value of the treated fabric sample is 81, which indicates that the rust stains on the fabric sample are 100% removed after treatment (i.e., the rust removal rate is 100%).

[0129] As shown in Table 1B, conventional 10% hydrofluoric acid solution can provide about 98% rust removal rate; while 10% oxalic acid solution only provides about 47% rust removal rate. Tested compositions #1G (7 wt% oxalic acid) and #1J (12 wt% oxalic acid) can provide about 95% and 93% rust removal rates, respectively.

[0130] Table 1C shows the flowability values ​​of fabric swatches after treatment with the tested rust stain removal compositions. The reference is a rust stained fabric swatch without any rust removal treatment. Two known rust stain removal compositions were used for the comparative study: A rust remover, which is widely used and is considered to be a conventional fabric rust remover, which contains 10% by weight (based on the total weight of the rust remover) of hydrofluoric acid as an active ingredient (hereinafter referred to as "10% hydrofluoric acid solution"); and another commercially available fabric rust remover, which contains 10% by weight (based on the total weight of the rust remover) of oxalic acid as an active ingredient (hereinafter referred to as "10% oxalic acid solution").

[0131] Table 1C

[0132]

[0133] The reference is a rusty fabric sample without any rust removal treatment, and its flowability value is 9.0 poise. -1 The higher the flowability value of the fabric sample, the higher the percentage loss of tensile strength of the fabric caused by the rust removal treatment. The higher the change in the % flowability value, the higher the degree of undesirable fabric damage caused by the rust removal treatment.

[0134] As shown in Table 1C, upon using a conventional 10% hydrofluoric acid solution as the rust stain removal composition, the treated fabric swatch lost about 44% of its fluidity value. Upon using a 10% oxalic acid solution as the rust stain removal composition, the treated fabric swatch lost about 28% of its fluidity value. On the other hand, the tested compositions #1E and #1G provided fluidity value losses of only 2% and 6%, respectively. The tested composition #1J provided a fluidity value loss of 24%, which is about half of the loss obtained with a conventional 10% hydrofluoric acid solution, but still less than the loss obtained with a 10% oxalic acid solution.

[0135] Example 2

[0136] The reflectance R460 value of the rust-stained fabric sample used in this study was about 5±1. The rust-stained fabric sample was subjected to a 5-minute rust removal treatment using the tested rust stain removal composition using a one-step method. The efficacy of the tested rust stain removal composition in removing rust from the stained fabric sample was determined based on the reflectance R460 value.

[0137] Table 2 shows the reflectance R460 values ​​of fabric swatches after treatment with the tested rust stain removal compositions containing ascorbic acid as the sole rust removal active ingredient. Test compositions #2A to #2E were aqueous solutions containing different concentrations of ascorbic acid, ranging from about 0.5% by weight ascorbic acid for test composition #2A to about 7% by weight ascorbic acid for test composition #2E.

[0138] Table 2

[0139] #2A #2B #2C #2D #2E ascorbic acid 0.5% 1% 3% 6% 7% Water (up to 100%) Average reflectivity R460 value 6.28 7.00 6.25 6.99 6.66 %Rust removal rate 8% 9% 8% 9% 8%

[0140] As shown in Table 2, regardless of the amount (wt%) of ascorbic acid in the tested compositions #2A to #2E, the average reflectance R460 values ​​of the treated fabric swatches were approximately the same. Therefore, the amount of ascorbic acid in the tested rust stain removal compositions had little or no effect on the rust removal efficacy of the stained fabric.

[0141] In addition, the average reflectance R460 value of the stained fabric swatches after treatment with the tested rust stain removal composition was approximately the same as the average reflectance R460 value of the stained fabric swatches before treatment. This indicates that ascorbic acid itself has very poor rust removal effect on stained fabrics.

[0142] Example 3

[0143] Table 3A shows the reflectance R460 values ​​of rust-stained fabric swatches after treatment with the tested rust stain removal compositions in a one-step rust removal treatment. The tested rust stain removal compositions contained different concentrations of ascorbic acid. Tested composition #3A contained oxalic acid as the sole rust removal active ingredient. Tested compositions #3B to #3N contained both oxalic acid and ascorbic acid as rust removal active ingredients, but at different concentrations of ascorbic acid. The concentrations of ascorbic acid in the tested compositions ranged from about 0.5% by weight for tested composition #3B to about 9% by weight for tested composition #3N.

[0144]

[0145] Figure 1 is a graph plotting the relationship between % rust removal and the amount of ascorbic acid (by weight, based on the total weight of the tested rust stain removal composition). Surprisingly and unexpectedly, a significant increase in % rust removal was observed when the amount of ascorbic acid was above 0.5 wt % but below 7 wt % (based on the total weight of the tested rust stain removal composition), such as from about 1 wt % to about 6 wt % (based on the total weight of the tested rust stain removal composition). Thus, the presence of certain specific concentration ranges of ascorbic acid in the tested rust stain removal compositions unexpectedly and significantly increased the % rust removal on stained fabric swatches.

[0146] Table 3B shows the flow values ​​of the fabric swatches after treatment with the tested rust stain removal compositions.

[0147] Table 3B

[0148]

[0149] As shown in Table 3B, once the conventional 10% hydrofluoric acid solution was used as the rust stain removal composition, the fluidity value of the treated fabric sample was lost by about 44%. Once the 10% oxalic acid solution was used as the rust stain removal composition, the fluidity value of the treated fabric sample was lost by about 28%. On the other hand, the fluidity values ​​of the tested compositions #3B, #3F, and #3L were lost by only 1%, 6%, and 19%, respectively.

[0150] Example 4

[0151] Table 4 shows the average reflectance R460 values ​​of the rust-stained fabric swatches after treatment with the tested rust stain removal compositions in a one-step rust removal treatment. The tested rust stain removal compositions contained different concentrations of sulfamic acid. Test composition #4A did not contain sulfamic acid. Test compositions #4B to #4E contained different concentrations of sulfamic acid, ranging from about 0.5% by weight of test composition #4B to about 3% by weight of test composition #4E.

[0152] Table 4

[0153]

[0154]

[0155] Regardless of the amount (wt%) of sulfamic acid in the tested compositions #4A to #4E, the average reflectance R460 values ​​of the treated fabrics were approximately the same. Thus, the amount of sulfamic acid in the tested rust stain removal compositions had essentially no effect on the % rust removal of the stained fabrics.

[0156] Example 5

[0157] Table 5 below summarizes the rust removal efficacy and fabric damage levels of the different rust stain removal compositions used on rust stained fabric swatches as shown in Examples 1 and 3.

[0158]

[0159] Example 6

[0160] The rust stained fabric swatches were subjected to a two-step rust removal treatment wherein the stained fabric swatches were contacted with a first composition for about 10 to 20 seconds and then with a second composition for 5 minutes.

[0161] Table 6 shows various first compositions used in the study, which contain different concentrations of ascorbic acid for rust removal, as well as sodium bisulfite, sorbitol, a surfactant, isopropyl alcohol as an organic solvent, and the balance of water. Tested composition #6A does not contain ascorbic acid. Tested compositions #6B to #6K contain ascorbic acid in an amount ranging from about 0.5% by weight of tested composition #6B to about 6% by weight of tested composition #6K.

[0162] Table 6

[0163]

[0164] *Water balance to 100%

[0165] The second composition used in the second step of the treatment is an aqueous solution containing 10% by weight (based on the total weight of the second composition) of oxalic acid as a rust removing active ingredient and monoethanolamine and the balance of water ("10% oxalic acid solution").

[0166] Table 7A shows a comparison of the % rust removal of stained fabric swatches after treatment with different rust stain removal compositions. The average reflectance R460 value of a fabric swatch containing no rust stains and without any rust removal treatment (ie, the "reference") is also recorded.

[0167] The reference is a fabric sample without rust stains and without any rust removal treatment, and its average reflectance R460 value is 81 ± 1. The higher the reflectance R460 value, the higher the whiteness level of the fabric, and therefore the better the rust stain removal composition is in removing rust stains from the stained fabric.

[0168]

[0169] Treatment No. I (treatment with 10% hydrofluoric acid solution) provided an average reflectance R460 value of about 79, which corresponds to a rust removal rate of about 98%.

[0170] Treatment No. II (treatment using only 10% oxalic acid solution) provided an average reflectance R460 value of about 38, which corresponds to only about 47% rust removal.

[0171] Treatment No. III (a two-step treatment using Test Composition #6A containing 0 wt. % ascorbic acid followed by a 10% oxalic acid solution) provided an average reflectance R460 value of 42, which corresponds to only about 51% rust removal. The reflectance R460 values ​​for Treatment Nos. II and III are approximately the same because both treatments rely on oxalic acid as the sole rust removal active ingredient and at the same concentration (10 wt. % oxalic acid).

[0172] Treatment Nos. IV to XII were two-step treatments, wherein the first step was a treatment with a first composition containing ascorbic acid (i.e., test compositions #6B to #6K, respectively), followed by a second step of treatment with a 10% oxalic acid solution. As shown in Table 7A, Treatment Nos. IV to XII all exhibited significant enhancements in rust removal efficacy (% Rust Removal of approximately 100%) compared to Treatment Nos. II or III, which relied on the use of oxalic acid as the sole rust removal active ingredient (% Rust Removal of approximately 47% to approximately 51%).

[0173] Table 7B shows the flow values ​​of the fabric swatches after treatment with the tested rust stain removal compositions.

[0174] Table 7B

[0175]

[0176] As shown in Table 7B, when a conventional 10% hydrofluoric acid solution was used as the rust stain removal composition (Treatment No. I), the treated fabric swatches lost about 44% of their fluidity values. When a 10% oxalic acid solution was used as the rust stain removal composition (Treatment No. II), the treated fabric swatches lost about 28% of their fluidity values. Treatment No. IV (a 2-step treatment using Test Composition #6B containing 0.5 wt. % ascorbic acid followed by a 10% oxalic acid solution) caused a 24% loss of fluidity values. Treatment No. XII (a 2-step treatment using Test Composition #6K containing 6 wt. % ascorbic acid followed by a 10% oxalic acid solution) caused a 30% loss of fluidity values.

[0177] Various features and advantages of the invention are set forth in the following claims.

Claims

1. A synergistic rust stain removal composition for fabrics, comprising: oxalic acid in an amount greater than about 1 weight percent but less than about 13 weight percent based on the total weight of the composition; Ascorbic acid in an amount greater than about 0.5 weight percent but less than 7 weight percent based on the total weight of the composition; and water.

2. The composition of claim 1, wherein oxalic acid is present in an amount greater than about 6 weight % but less than about 13 weight % based on the total weight of the composition.

3. The composition of claim 1, wherein oxalic acid is present in an amount of about 2 weight % to about 12 weight % based on the total weight of the composition.

4. The composition of claim 1, wherein oxalic acid is present in an amount of about 3 weight % to about 12 weight % based on the total weight of the composition.

5. The composition of claim 1, wherein oxalic acid is present in an amount of about 7 weight % to about 12 weight % based on the total weight of the composition.

6. The composition according to any one of the preceding claims, wherein ascorbic acid is present in an amount of about 1 wt% to about 6 wt% based on the total weight of the composition.

7. The composition according to any one of the preceding claims, wherein the composition further comprises a pH adjuster, an organic solvent, a surfactant, a chelating agent, an acrylic polymer, an oxidizing agent, a fragrance, a dye, or any combination thereof.

8. The composition according to claim 7, wherein the composition satisfies at least one of the following: (a) the pH adjuster comprises aminosulfonic acid, ethanolamine, sodium bisulfite or any mixture thereof; (b) the organic solvent comprises glycol ether, alcohol, ethylene glycol or a mixture thereof; (c) The surfactant comprises an anionic surfactant, a nonionic surfactant or any combination thereof.

9. The composition of claim 8, wherein the anionic surfactant comprises sodium lauryl sulfate, sodium alkylbenzene sulfonate, or a mixture thereof.

10. A composition according to any one of the preceding claims, wherein the composition consists of: oxalic acid in an amount greater than about 1 weight percent but less than about 13 weight percent based on the total weight of the composition; ascorbic acid in an amount greater than about 0.5 weight percent but less than about 7 weight percent based on the total weight of the composition; water; and The optional at least one additive is selected from a pH adjuster, an organic solvent, a surfactant, a chelating agent, an acrylic polymer, an oxidizing agent, a fragrance, a dye or any combination thereof.

11. The composition according to claim 10, wherein oxalic acid is present in an amount of about 2 wt% to about 12 wt%, preferably about 7 wt% to about 12 wt%, based on the total weight of the composition.

12. The composition of claim 10 or 11, wherein ascorbic acid is present in an amount of about 2 weight % to about 6 weight % based on the total weight of the composition.

13. The composition of any one of the preceding claims, wherein the composition does not contain hydrogen peroxide, inorganic acids, organic acids other than oxalic acid and ascorbic acid, fluoride-based salts, or any combination thereof.

14. The composition according to claim 13, wherein: (a) the inorganic acid comprises hydrofluoric acid, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, boric acid, or any combination thereof; (b) the other organic acids include formic acid, acetic acid, fumaric acid, citric acid, malic acid, tartaric acid, ethane-1-hydroxy-1,1'-diphosphonic acid, fatty acids, or any combination thereof; or (c) The fluoride-based salt comprises calcium fluoride, sodium fluoride, ammonium bifluoride, or any combination thereof.

15. A method of removing rust stains from fabrics, comprising contacting the fabrics with the rust stain removing composition according to any one of claims 1 to 14.

16. The method of claim 15, wherein the contact time is from about 1 minute to about 20 minutes, preferably about 5 minutes.

17. A method for removing rust stains from fabric, comprising: contacting the fabric with a first aqueous solution comprising from about 0.5 weight percent to about 6 weight percent ascorbic acid based on the total weight of the first aqueous solution; and The fabric is contacted with a second aqueous solution comprising from about 1 weight percent to about 12 weight percent oxalic acid based on the total weight of the second aqueous solution.

18. The method of claim 17, wherein the method comprises contacting the fabric with a first aqueous solution and subsequently contacting the fabric with a second aqueous solution.

19. The method of claim 17, wherein the method comprises contacting the fabric with the second aqueous solution and subsequently contacting the fabric with the first aqueous solution.

20. The method of claim 17, wherein the method comprises contacting the fabric with a first aqueous solution and a second aqueous solution simultaneously.

21. The method according to any one of claims 17 to 20, wherein the fabric is contacted with the first aqueous solution and the second aqueous solution for about 1 minute to about 20 minutes, preferably about 5 minutes.

22. The method according to any one of claims 17 to 21, wherein the method satisfies at least one of the following: (a) the first aqueous solution comprises ascorbic acid in an amount from about 0.5%, about 1.0%, about 1.5%, about 2%, about 2.5%, about 3%, or about 3.5% by weight based on the total weight of the first aqueous solution to about 4%, about 4.5%, about 5.0%, about 5.5%, or about 6.0% by weight based on the total weight of the first aqueous solution; (b) the second aqueous solution comprises oxalic acid in an amount ranging from about 1%, about 2%, about 3%, about 4%, about 5%, about 6% or about 7% by weight to about 8%, about 9%, about 10%, about 11% or about 12% by weight based on the total weight of the second aqueous solution.

23. The method of any one of claims 17 to 22, wherein the method provides a rust removal percentage of at least 50%, the rust removal percentage calculated based on the reflectance of the fabric at a wavelength of 460 nanometers.

24. The method according to any one of claims 17 to 23, wherein the change in fluidity value of the fabric between before and after contact with the rust stain removing composition is not more than 25%, said change in fluidity value being determined according to Indian Standard IS244 (1984) (Second Revision, Redetermined in 2006).

25. The method of any one of claims 17 to 24, wherein the contacting is performed at room temperature.